Does being stricter mean doing better? Different effects of environmental policy stringency on quality of life, green innovation, and international cooperation - Prokop, Viktor; Gerstlberger, Wolfgang; Vrabcová, Pavla; Zapletal, David; Sein, Yee Yee (Heliyon, 2023)
Nowadays, when we are facing several strict regulations, the question arises - does higher strictness lead to the desired results? This study addresses the fact that less research attention has focused on the effects of environmental policy stringency (EPS) on perceived health expressing quality of life, and on green international cooperation. In addition, previous research has provided rather mixed results on the impact of EPS on green innovation. Therefore, we fill an interesting research gap and help better understand the relationship between market-based and non-market-based EPS, perceived health, green innovations, and green international cooperation in OECD (Organization for Economic Co-operation and Development) countries. Using three complementary databases provided by OECD, Eurostat, and the World Bank and the classical linear regression model, we confirm hypotheses that strong market-based EPS and green international cooperation have positive effects on perceived health. Surprisingly, contrary to the findings of prior research, we do not confirm the positive effects of market-based and non-market-based EPS on green international cooperation. This study contributes to the literature on the Porter hypothesis, technological collaborations in green technological development, and environmental innovation theory. In addition, this study provides several practical implications for policymakers across OECD countries.
Keywords: Environmental policy stringency; Sustainable development; International collaboration; Patents; Perceived health